2021
DOI: 10.1093/mnras/stab456
|View full text |Cite
|
Sign up to set email alerts
|

Impact of photochemical hazes and gases on exoplanet atmospheric thermal structure

Abstract: We investigate the impact of photochemical hazes and disequilibrium gases on the thermal structure of hot-Jupiters, using a detailed 1-D radiative-convective model. We find that the inclusion of photochemical hazes results in major heating of the upper and cooling of the lower atmosphere. Sulphur containing species, such as SH, S2 and S3 provide significant opacity in the middle atmosphere and lead to local heating near 1 mbar, while OH, CH, NH, and CN radicals produced by the photochemistry affect the thermal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 103 publications
3
38
0
Order By: Relevance
“…The red triangles are the data presented in Sing et al (2016) (only that blueward of 6500 Å is displayed) -the errorbars on those points are too small to be seen on this scale. The green solid line is that expected by the 1-D model extended from the work of Lavvas & Arfaux (2021), and the black dashed line is that expected by the 3-D model extended from the work of Steinrueck et al (2020). The Roche lobe of the planet (3 R opt , or 𝑅 p /𝑅 * = 0.471) is too far off the scale of the plot to be visible.…”
Section: Discussionmentioning
confidence: 91%
“…The red triangles are the data presented in Sing et al (2016) (only that blueward of 6500 Å is displayed) -the errorbars on those points are too small to be seen on this scale. The green solid line is that expected by the 1-D model extended from the work of Lavvas & Arfaux (2021), and the black dashed line is that expected by the 3-D model extended from the work of Steinrueck et al (2020). The Roche lobe of the planet (3 R opt , or 𝑅 p /𝑅 * = 0.471) is too far off the scale of the plot to be visible.…”
Section: Discussionmentioning
confidence: 91%
“…From a theoretical perspective, recent studies have also shown that thermal inversions could occur naturally in the upper atmosphere of hot Jupiters (Lothringer et al 2018;Lavvas & Arfaux 2021). For example, the day side of irradiated hot Jupiters might be significantly heated by photochemical hazes and/or dissociation of the main molecules and the addition of continuum opacity from negative hydrogen (H -).…”
Section: Full Retrievalmentioning
confidence: 99%
“…For example, the day side of irradiated hot Jupiters might be significantly heated by photochemical hazes and/or dissociation of the main molecules and the addition of continuum opacity from negative hydrogen (H -). In addition, local thermal inversions are also predicted to occur if sulfur-bearing species are present (Lavvas & Arfaux 2021). While the investigations in Lothringer et al (2018) were performed on an F-type star with a larger UV flux than WASP-43 (K-type), their fiducial hot-Jupiter simulations showed that planets at distances from their host star similar to WASP-43 b (0.1 au) and with equilibrium temperatures around 1500 K could display inversions above 100 Pa, regardless of their TiO/ VO content.…”
Section: Full Retrievalmentioning
confidence: 99%
“…Large particles scatter very efficiently, introducing significant opacity to an atmosphere, which obscures the spectral features of other molecules and fundamentally alters the thermal balance throughout an atmosphere (Arney et al 2016(Arney et al , 2017(Arney et al , 2018Lavvas & Arfaux 2021). The refractive index of experimentally-produced aerosol condensate is influenced by the chemical composition of the gas mixture in which it was produced, and may also be dependent on the energy source used to generate the particles (Hasenkopf et al 2010;Mahjoub et al 2012;Gavilan et al 2017Gavilan et al , 2018He et al 2018;Ugelow et al 2018).…”
Section: Modelling Aerosolsmentioning
confidence: 99%